Lifelong Learning in Methods of Dramatherapy for Staff Working With People With Disabilities - Silarova, Jana; Silarova, Lenka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Topic of this article is about lifelong learning for staff who works within the homes of people with intellectual disorder in using methods of drama therapy. The project particularly emphases on the education using these methods within institutions, where clients live and workers are employed. The advantage of this approach is that workers know them well, so they can promote clients’ participation and observe their progress during the process.